Myricitrin as the main constituent of two species of Myrcia - Henrique H. Morescoa, Marcos Pereiraa, Lizandra C. Bretanhaa, Gustavo A. Mickeb, Moacir G. Pizzolattia, Ines M. C. Brighentea (Journal of Applied Pharmaceutical Science, 2014)
Myricitrin was isolated as the major constituent from Myrcia splendens (2 g %) and Myrcia palustris (0.5g %) of their fractions soluble in ethyl acetate. The presence of this compound was confirmed by chromatographic analyses using HPLC-DAD. The antioxidant activity was measured using reducing power in relation to the reduction of iron (III) to iron (II) ions and DPPH radical scavenging assay. The ethyl acetate and butanol fractions showed the highest antioxidant activity for both species. In relation to the ability of the sample to scavenge DPPH radicals the EC50 values were 8.44 and 9.35 µg/ mL for M. splendens and 17.83 and 15.34 µg/ mL for M. palustris for the ethyl acetate and butanol fractions, respectively. The antioxidant activity may be related to the myricitrin in these extracts that showed an EC50 = 13.93 µg/mL.
Keywords: Antioxidants,myricitrin,Myrcia palustris,Myrcia splendens.